Intensidad y distribución en energía de picos suma en espectroscopia de fluorescencia de rayos-X dispersiva en energía - Bravo, Jorge (2022)
Radiation detection systems allow registering sum peaks as a consequence of their finite time resolution. In order to interpret the accumulated spectra properly it is necessary to be able to predict the presence of these sum peaks in order to identify correctly the peaks that are observed in the spectra, especially those of very low intensity. In this work a detailed analysis of the presence of sum peaks of order two is presented for the case of energy dispersive X-ray fluorescence spectrometry.